Assessing effects of social interaction on early development of executive function in infants - Tan, Xing Xi (Nanyang Technological University, 2023)
This thesis dissertation is made up of two sections: Section 1 - Interactive Executive Function Tasks for Parent-Infant Dyads and Section 2 - Comparing parent-infant and stranger-infant interaction effects on infant attentional set-shifting.